Acellular Derivatives of Mesenchymal Stem Cells Prevent Peritoneal Adhesions in an Animal Model - (:unkn) unknown (Academic Press, 2018)
Background: Peritoneal adhesions are nonanatomical connections that bind organs to the abdominal wall or among them. They arise after peritoneal injury, which triggers an inflammatory response followed by a healing process that leads to fibrotic tissue formation. Mesenchymal stem cells and their secretion products, also referred to as acellular derivatives (ACDs), have anti-inflammatory, fibrinolytic, and antifibrogenic properties. The aim of this study was to determine the effect of intraoperative administration of ACD on the appearance, severity, and progression of peritoneal adhesions, in an animal model. Materials and methods: Cecal erosions were mechanically induced in adult mice. Before closure, the vehicle, ACD, or Seprafilm was administered. Seven days later, the presence and grade of peritoneal adhesions were assessed macroscopically. One, 3, and 7 d after intervention, molecular and cellular markers of inflammation, fibrinolysis, and fibrogenesis were evaluated both locally and systemically. Results: ACDs avoided the appearance of clinically relevant peritoneal adhesions. The vehicle had no effect, and Seprafilm reduced them inconsistently. The antiadhesive effect of ACD was associated with an early reduction of proinflammatory cytokine (tumor necrosis factor-alpha and interferon-gamma) secretion and leukocyte (polymorphonuclears, mononuclears, and macrophages) infiltration. High levels of D-dimer, low fibrin deposits, low myofibroblasts infiltration, and less fibrosis were also observed. Conclusions: ACD administered at the end of abdominal surgeries prevents the formation of peritoneal adhesions due to the modulation of inflammatory, fibrinolytic, and fibrogenic processes. (C) 2017 Elsevier Inc. All rights reserved.